Biomimetic synthesis of proline-derivative templated mesoporous silica for increasing the brain distribution of diazepam and improving the pharmacodynamics of nimesulide. (1st January 2017) - Li, Heran; Wang, Jianxin; Cong, Jialiang; Wei, Chen; Li, Jing; Liu, Hongzhuo; Li, Sanming; Yang, Mingshi
Abstract: Herein a new kind of proline-derivative templated mesoporous silica with curved channels (CMS) was biomimetically synthesized and applied as carrier to improve the drug dissolution and bioavailability of hydrophobic diazepam (DZP) and nimesulide (NMS). Drugs can be incorporated into CMS with high efficiency; during this process, they successfully transformed to amorphous phase. As a result, the dissolution rate of DZP and NMS was significantly improved. Biodistribution study confirmed that CMS converted DZP distribution in mice with the tendency of lung targeting and brain targeting. At 45 min postadministration, the concentrations of DZP in plasma, lung and brain were 8.57-fold, 124.94-fold and 19.55-fold higher from 1:3 DZP/CMS sample than that of pure DZP sample, respectively. At 90 min postadministration, the content of DZP in brain was 62.31-fold higher for 1:3 DZP/CMS sample than that of pure DZP. Besides, the anti-inflammatory and analgesic effects of 1:3 NMS/CMS were systematic evaluated using mouse ankle swelling test (MAST), mouse ear swelling test (MEST) and mouse writhing test (MWT). The results indicated that after incorporating into CMS, the therapeutic effects of NMS were obviously improved, and the inhibition rates of 1:3 NMS/CMS in all pharmacodynamics tests varied from 102.2% to 904.3%.